2007
DOI: 10.3402/polar.v26i2.6226
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of soft-bottom molluscs in the Bellingshausen Sea and around Peter I Island

Abstract: Macrobenthic soft-bottom molluscs were sampled in 30 stations located in the Bellingshausen Sea at depths ranging from 90 to 3304 m. The samples were collected using a quantitative grab box-corer during the cruises BENTART 03, from 24 January to 3 March 2003, and BENTART 06, from 2 January to 16 February 2006. Molluscs represent 1074 specimens belonging to 62 species of Polyplacophora, Gastropoda, Bivalvia and Scaphopoda. The bivalve Cyamiocardium denticulatum was the most abundant species (448 specimens). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
2
Order By: Relevance
“…The meroplankton community in the Bellingshausen Sea was dominated by gastropod larvae, in contrast to reports by Shreeve and Peck (1995) who found a lower abundance of gastropod larvae, except at the outer open water station, pointing out that these larvae may be swept offshore by currents or may be produced by deep-water or holoplanktonic species. This appears likely since the gastropod adults that reproduce via pelagic larvae are not very abundant in the BS (Troncoso et al 2007;Sáiz et al 2008). Troncoso et al (2007) observed mainly bivalve in the benthos, but the presence of bivalve veligers in the samples was anecdotal, which may indicate that the larvae live demersally (Hain and Arnaud 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meroplankton community in the Bellingshausen Sea was dominated by gastropod larvae, in contrast to reports by Shreeve and Peck (1995) who found a lower abundance of gastropod larvae, except at the outer open water station, pointing out that these larvae may be swept offshore by currents or may be produced by deep-water or holoplanktonic species. This appears likely since the gastropod adults that reproduce via pelagic larvae are not very abundant in the BS (Troncoso et al 2007;Sáiz et al 2008). Troncoso et al (2007) observed mainly bivalve in the benthos, but the presence of bivalve veligers in the samples was anecdotal, which may indicate that the larvae live demersally (Hain and Arnaud 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This appears likely since the gastropod adults that reproduce via pelagic larvae are not very abundant in the BS (Troncoso et al 2007;Sáiz et al 2008). Troncoso et al (2007) observed mainly bivalve in the benthos, but the presence of bivalve veligers in the samples was anecdotal, which may indicate that the larvae live demersally (Hain and Arnaud 1992).…”
Section: Discussionmentioning
confidence: 99%
“…According to the few published papers on a number of benthic taxa, including molluscs (Troncoso et al 2007;Troncoso and Aldea 2008) and polychaetes (Parapar et al in press) as well as when considering higher taxonomic categories (Sáiz et al 2008), the Bellingshausen Sea seems to be a well-defined biogeographical area within the Southern Ocean. This fact has tentatively been related to depth and the very nature of the sediment, which is mostly composed by deposits of foraminiferans and diatoms (Hillenbrand et al 2003).…”
Section: General Remarksmentioning
confidence: 99%
“…2004). The Bellingshausen Sea has been the object of several recent Spanish oceanographic cruises (BENTART 2003 and BENTART 2006), and the first studies are now starting to appear (molluscs, Troncoso et al. [2007]; soft‐bottom community, Saiz et al.…”
mentioning
confidence: 99%